L’occhio performante: la fotografia come strumento di costruzione del freak ottocentesco - D’Amico, Flavia Dalila (Rivista di studi di fotografia. Journal of Studies in Photography, 2018)
This paper highlights the complex construction of the meaning of the freak body operated by photographic practices in the 19th century. One of the first uses of the medium was the documentation of patients as a way to legitimate modern medical discourses on the body. The aim of this study is to stress photography’s role in the creation of categories such as “disability,” “deviant,” and “extraordinary”. The analysis focuses on Charles Eisenmann’s freak portraits, which can be read as a popularization of the general trend toward the classification of human diversity in the exhibition of disabled bodies.